Morphological and physiological responses of Cedrela Fissilis Vellozo (Meliaceae) seedlings to light - Santos,Débora Leonardo dos (2006)
Seeds of Cedrela fissilis Vellozo were planted and maintained under two distinct conditions: at east border of a forest with red: far-red ratio of 1.15 and under canopy with photosynthetic photon flux density of 0.22-7% of full sun radiation and red: far-red ratio of 0.21-0.36. Seedling growth (height and stem diameter) was faster under sun, the development of roots more continuous and the number of leaves almost twice of that of shade plants. The leaf area was 10 times greater in sun plants with 15-25 leaflets per leaf while under shade only 5 to 10 leaflets were found per leaf. In shade plants, a higher proportion of dry mass was found in aerial parts. Leaves of sun plants had the capacity of gas exchange to respond to high light radiation, but leaves adapted to shade presented a lower response to light changes. When shade plants were transferred and maintained under the sun for 15 days, only the young leaves were adapted to increased light radiation, reaching the same photosynthetic rate as sun plants, while old leaves were shed. Sun plants transferred to shade conditions did not lose leaves, but did not reach the same photosynthetic rate attained by shade plants.